2014
DOI: 10.1186/s13058-014-0420-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel AMPK-PEA15 axis in the anoikis-resistant growth of mammary cells

Abstract: IntroductionMatrix detachment triggers anoikis, a form of apoptosis, in most normal epithelial cells, while acquisition of anoikis resistance is a prime requisite for solid tumor growth. Of note, recent studies have revealed that a small population of normal human mammary epithelial cells (HMECs) survive in suspension and generate multicellular spheroids termed ‘mammospheres’. Therefore, understanding how normal HMECs overcome anoikis may provide insights into breast cancer initiation and progression.MethodsPr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 51 publications
(79 reference statements)
10
77
0
Order By: Relevance
“…In agreement with a previous study [36], down-regulation of PEA15 resulted in significant decreases in the number of viable cells (Fig. 7B) and cell viability (Fig.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with a previous study [36], down-regulation of PEA15 resulted in significant decreases in the number of viable cells (Fig. 7B) and cell viability (Fig.…”
supporting
confidence: 93%
“…PEA15 is a multi-functional protein that has been implicated in the regulation of major intracellular processes including proliferation and apoptosis, and its function is tightly regulated by its phosphorylation at two serine residues, Ser104 and Ser116 [27]. Both CaMKII and AKT phosphorylate PEA15 at Ser116 [47][48][49] and, more recently, AMPK was reported to act as an upstream kinase of PEA15 in both normal and cancerous breast epithelial cells [36]. Phosphatases play an equally important role as kinases in regulating the phosphorylation state of PEA15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mei et al42 further showed that p38 MAPK activation contributes to an increase in CSC population and metastasis. It has been reported that radioresistant glioblastoma stem cells acquired enhanced AMPK activity and in normal human mammary epithelial cells AMPK mediated the mammosphere formation, indicating that AMPK might involve in regulating the self‐renewal and therapeutic resistance of CSCs 38, 39. Our study showed that Sme induced apoptosis via activating the p38 MAPK and AMPKα pathways in MCF7‐Nanog cells.…”
Section: Discussionsupporting
confidence: 49%
“…There is growing evidence supporting that p38 MAPK and AMPK play crucial roles in cancer cell growth, proliferation, survival 38, 39, 40. Meng et al41 reported that p38 MAPK exhibits overexpression in highly metastatic human and mouse breast cancer cell lines and promotes basal‐like and metastatic properties in breast tumor samples.…”
Section: Discussionmentioning
confidence: 99%